Town and village (differnces and interdependence) in the work of Dragoljub Jovanović - Živić, Nikola; Radovanović, Nemanja (Sociološki pregled, 2022)
In his scientific and political work, Dragoljub Jovanović was interested, more than in anything else, in issues of the village and the peasantry. There is a large and diverse number of topics and problems elaborated by D. Jovanović within the mentioned question. The paper will discuss Jovanović’s views on the village and the city, i.e. differences and interdependence between these two types of settlements. We have tried to see Jovanović’s understanding of the relationship between the village and the town at several levels, bearing in mind that in his papers the town almost always appears in the service of a better understanding of the village and the peasant. The paper is based on the analysis of Dragoljub Jovanović’s available papers, as well as the literature that deals with the author’s life and work. Where necessary, we have also considered other relevant literature related to the topic of the paper. Taking into account the fact that D. Jovanović’s work is insufficiently known in the field of sociology, the aim of the research was to find relevant sociological insights of this author into the relationship between the village and the town. We believe this is also supported by the fact that a great deal of these considerations is still relevant today.